Potassium fertilizer promotes the thin-shelled Tartary buckwheat yield by delaying senescence and promoting grain filling - Tang, Lulu; Tang, Jingang; Huang, Kaifeng; Huang, Xiaoyan (Frontiers in Plant Science, 2024)
The application rate of potassium fertilizer is closely related to the yield of crops. Thin-shelled Tartary buckwheat is a new variety of Tartary buckwheat with the advantages of thin shell and easy shelling. However, little is known about application rate of potassium fertilizer on the yield formation of thin-shelled Tartary buckwheat. This study aimed to clarify the effect of potassium fertilizer on the growth and yield of thin-shelled Tartary buckwheat. A field experiment to investigate the characteristics was conducted across two years using thin-shelled Tartary buckwheat (Miku 18) with four potassium fertilizer applications including 0 (no potassium fertilizer, CK), 15 (low-concentration potassium fertilizer, LK), 30 (medium-concentration potassium fertilizer, MK), and 45 kg·ha−1 (high-concentration potassium fertilizer, HK). The maximum and average grain filling rates; starch synthase activity; superoxide dismutase and peroxidase activities in leaves; root morphological indices and activities; available nitrogen, phosphorus, and organic matter content in rhizosphere soil; urease and alkaline phosphatase activities in rhizosphere soil; plant height, main stem node number, main stem branch number, leaf number; grain number per plant, grain weight per plant, and 100-grain weight increased first and then decreased with the increase in potassium fertilizer application rate and reached the maximum at MK treatment. The content of malondialdehyde was significantly lower in MK treatment than in other three treatments. The yields of thin-shelled Tartary buckwheat treated with LK, MK, and HK were 1.22, 1.37, and 1.07 times that of CK, respectively. In summary, an appropriate potassium fertilizer treatment (30kg·ha−1) can delay the senescence, promote the grain filling, and increase the grain weight and final yield of thin-shelled Tartary buckwheat. This treatment is recommended to be used in production to achieve high-yield cultivation of thin-shelled Tartary buckwheat.